Schrodinger's nuisance update in the jurisprudence on nuisance - Frabelle Properties Corp. v. AC Enterprises, Inc. (2021)
This Comment presents an update in the jurisprudence on nuisance. From the introduction of the concept of nuisance through early laws and jurisprudence, until the development of a statutory definition of nuisance under the New Civil Code, the legal understanding of what precisely constitutes a nuisance has significantly varied. This is perhaps due to the manner in which nuisance was defined-its definition having been described as comprehensive by the Supreme Court, owing to the concept's elastic design by nature. Notably, it is virtually impossible to statutorily define each and every nuisance because of the unique and evolving genetics, personality, and preferences of a person, which are among the factors that affect one's appreciation of a nuisance. On November 3, 2020, the Supreme Court promulgated FrabellePropertiesCorp. v. ACEnterprises,Inc., penned by then Chief Justice Diosdado M. Peralta. The case is a significant update in jurisprudence because it consolidated and identified guidelines for the bench and bar in the determination of noise nuisance. This case tempered the elasticity of the concept of nuisance by defining its standards with more particularity.
Keywords: Jurisprudence; Nuisances; Noise pollution laws